Energy storage performance in Dy doped Na0.425Bi0.425Ca0.15TiO3 Pb-free ceramics. Issue 18 (15th December 2020) - Dong, Jia; Tang, Mingyang; Li, Yang; Lv, Jingwen; Yu, Kun; Liu, Yi; Wu, Fei; Yan, Yan; Liu, Gang
Abstract: High capacity for the dielectric capacitors are necessary for practical applications. Additionally, dielectric capacitors should have some degree of temperature and frequency stability to allow them to adapt to environmental changes. To fulfil these requirements, Na0.425 Bi0.425 Ca0.15 TiO3 - x Dy ( x = 0, 2, 5, and 10 at‰) (NBCT- x Dy) energy storage ceramics were produced using a traditional solid-state synthesis method. NBCT-5Dy achieved an excellent energy storage density of 2.35 J/cm 3 and a good efficiency of 78.32% at 210 kV/cm. In addition, the sample was tested at 150 kV/cm under variable temperature and frequency conditions, showed a stable energy storage density of 1.3 J/cm 3 and maintains excellent efficiency at 30–150 °C and 0.2–200 Hz. Furthermore, the dielectric constant of the sample was measured at 0–40 kV/cm, and exhibited less than 2% change over this range. These results confirmed that the sample had excellent energy storage density and good stability. In the pulse discharge performance test, a high power density (46.31 MW/cm 3 at 150 kV/cm) was obtained, indicating that this material has great application prospects in the pulse capacitor field in the future.